TO THE PROBLEM OF THE USE OF LEGAL TERMS AND DEFINITIONS (BASED ON THE EXAMPLES OF A COMPARATIVE ANALYSIS OF THE CIVIL CODE OF THE REPUBLIC OF KAZAKHSTAN) - Turarova Жумагуль Мухтаровна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The article examines the use issues of an identical legal terms and definitions of the Civil Code of the Republic of Kazakhstan.